2022
DOI: 10.1186/s13046-022-02355-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of RNA-splicing factor Lsm12 as a novel tumor-associated gene and a potent biomarker in Oral Squamous Cell Carcinoma (OSCC)

Abstract: Background Oral squamous cell carcinoma (OSCC) is one of the common cancers worldwide. The lack of specific biomarkers and therapeutic targets leads to delayed diagnosis and hence the poor prognosis of OSCC patients. Thus, it is urgent to identify effective biomarkers and therapeutic targets for OSCC. Methods We established the golden hamster carcinogenic model of OSCC induced by 7,12-dimethylbenz(a) anthrancene (DMBA) and used mRNA microarrays to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…It is one of the main factors participating in DNA damage induced by oxidative stress [15]. Heretofore, the research on the function of LSM12 in human malignant tumors is still very limited [16][17][18]. Here, we demonstrated that LSM12 is involved in cytopathologic and tumorigenic functions during CRC development through the regulation of CTNNB1 protein stability and CTTNB1-LEF1-TCF1 transcriptional complex formation.…”
Section: Discussionmentioning
confidence: 77%
“…It is one of the main factors participating in DNA damage induced by oxidative stress [15]. Heretofore, the research on the function of LSM12 in human malignant tumors is still very limited [16][17][18]. Here, we demonstrated that LSM12 is involved in cytopathologic and tumorigenic functions during CRC development through the regulation of CTNNB1 protein stability and CTTNB1-LEF1-TCF1 transcriptional complex formation.…”
Section: Discussionmentioning
confidence: 77%
“…The limitations in specific biomarkers and therapeutic targets for OSCC result in delayed diagnosis and poor prognosis in patients, which makes identification of novel biomarkers and treatment targets as urgent tasks for OSCC control. 15 In this work, we identified COL5A1 as a tumor driver in OSCC activated by GATA6. LINC00173, which could bind to GATA6 to block the transcriptional activation of COL5A1, was found to suppress the malignant phenotype of cancer cells.…”
Section: Discussionmentioning
confidence: 90%
“…LSM12 is significantly upregulated in OSCC tissues of patients and animal models. LSM12 is required for OSCC cell proliferation, migration, and tumorigenesis (45).…”
Section: Other Splicing Factorsmentioning
confidence: 99%
“…Full-length USO1 isoform was positively associated with OSCC cell proliferation and enhanced tumorigenic capacity, while USO1 short isoform without exon 15 showed the opposite effects on OSCC cell proliferation and cell cycle progression. LSM12 promotes USO1 exon 15 inclusion (45). Alternative RNA splicing and splicing factors regulate OSCC cell proliferation, invasion, and EMT.…”
Section: Uso1mentioning
confidence: 99%